The potential application of natural products in cutaneous wound healing: A review of preclinical evidence - Liu, E; Gao, Hongjin; Zhao, YiJia; Pang, Yaobing; Yao, Yejing; Yang, Zhengru; Zhang, Xueer; Wang, YanJin; Yang, Siming; Ma, Xiao; Zeng, Jinhao; Guo, Jing (Frontiers in Pharmacology, 2022)
Normal wound healing can be divided into three phases: inflammation, proliferation, and remodeling. The vast majority of wounds heal rapidly, but there is a large percentage of non-healing wounds for which substantial progress has still not been made. The factors affecting wound non-healing are complex and diverse, and nature, as a huge treasure trove of resources, from which to identify an effective solution becomes a key goal of research. This article attempts to highlight and review the mechanisms as well as targets of NPS for non-healing wound treatment. At present, the results of relevant studies have shown that NPS exert their effects are related to P13-AKT, P38MAK, FGF, MAPK, ERK signaling pathways and involve TGF, VEGF, TNF- α, IL-1β Expression of other cytokines and proteins. A systematic summary of the 25 NPS that contribute to wound healing was achieved by an inductive collation of the six major classes of compounds, including saponins, polyphenols, flavonoids, anthraquinones, polysaccharides, and others, which will further direct the attention to the active components of NPS and provide research ideas for further development of new products for wound healing.